Participatory Action Research-Based Guidance in Managing Students' Screen Time According to Islamic Values - Sari, Devit Etika; Wajdi, Muh Barid Nizarudin (LPPM Universitas Yudharta Pasuruan, 2024)
Proper guidance is needed to help students manage their use of technology and digital screens in a balanced way, to prevent negative impacts on their physical health, mental well-being, and religious values. This service aims to assist students in managing screentime wisely and strengthening religious values. A Participatory Action Research (PAR) approach involved students, teachers, and parents in three madrasahs in Nganjuk: MTSn Nglawak, MTSn Patianrowo, and MTS Termas Baron about 120 participants. Participatory Rural Appraisal (PRA) analysis methods, such as Ven Diagram, Flowchart, Timeline, Problem Tree, and Hope Tree, were applied. The service results show that screen time management training, discussion of religious values, active supervision, introduction of alternative activities, and education about the negative impact of screen time are relevant solutions. PAR-based mentoring can help students achieve a healthy digital balance by religious values, and provide guidance for practitioners and researchers in implementing similar mentoring.